"Sing Me Back Home:" Using Country Music to Clarify Criminological Theory in Undergraduate Courses. Issue 1 (2nd January 2023) - Stogner, John; Slate, Risdon; Blankenship, Chastity; McKee, Jesse
Abstract: The inclusion of music is central to early education pedagogy as an efficient means of conveying information and a mechanism for knowledge retention, yet these tools are generally omitted from higher educational approaches. Drawing on prior studies highlighting how musical assignments successfully supplemented traditional criminal justice coursework, a criminological theory course was redesigned with music as a core component. Musical selections were included and discussed in each class meeting as well as being tied to class assignments within a pilot course. Teaching techniques were refined over several semesters with the revised course framework including more student involvement, somewhat approaching a flipped classroom model whereby the instructor and students equally shared musical selections relevant to course curriculum. The instructor perceived students were more invested in the course. The professor-student dynamic also appeared to become more intimate due to both sharing music about which they were personally passionate. Further, the instructor's inclusion of crime-specific songs from older musical genres appeared to disrupt students' stereotypes associating crime with other genres and demographics. We offer a summary of the techniques for teaching a criminological theory course framed by instructor presentations of "outlaw" country music; guidance is also provided for utilizing other genres.